2011
DOI: 10.1099/mic.0.046870-0
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution and local differentiation in quinolone resistance in Pseudomonas aeruginosa

Abstract: The emergence and spread of antibiotic resistance in pathogens is a major impediment to the control of microbial disease. Here, we review mechanisms of quinolone resistance in Pseudomonas aeruginosa, an important nosocomial pathogen and a major cause of morbidity in cystic fibrosis (CF) patients. In this quantitative literature review, we find that mutations in DNA gyrase A, the primary target of quinolones in Gram-negative bacteria, are the most common resistance mutations identified in clinical samples of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…It has been observed before that highly resistant P. aeruginosa isolates harboring a double gyrA and parC mutation are isolated almost exclusively from non-CF patients, whereas in isolates from CF patients, single mutations within the QRDRs dominate (34,35,36). Interestingly, in accordance with the previous reports, 27 of the 29 gyrA parC mutants in this study were isolated from non-CF patients.…”
Section: Resultssupporting
confidence: 80%
“…It has been observed before that highly resistant P. aeruginosa isolates harboring a double gyrA and parC mutation are isolated almost exclusively from non-CF patients, whereas in isolates from CF patients, single mutations within the QRDRs dominate (34,35,36). Interestingly, in accordance with the previous reports, 27 of the 29 gyrA parC mutants in this study were isolated from non-CF patients.…”
Section: Resultssupporting
confidence: 80%
“…As is often observed in clinical strains of Gram-negative bacteria resistant to quinolones, all but three strains contained mutations in the QRDR of gyrA. Within this site we found five distinct mutations, four of which occur at two amino acid sites (83 and 87) known to be associated with binding of GyrA to DNA (Wong and Kassen 2011). No further mutations were found at the sites often associated with the primary incidences of quinolone resistance-gyrB, parC, or parE-among the subset of the top 18 chosen for further sequencing.…”
Section: Dna Sequence Variation Among Top 18 Mutantsmentioning
confidence: 81%
“…The observation of double mutants is not unusual, at least among clinical isolates of P. aeruginosa. Wong and Kassen (2011) showed that clinical isolates of fluoroquinolone-resistant P. aeruginosa often contain multiple mutations to both gyrases and efflux pumps and that the identity of the efflux pump mutation depends on whether the infection is acute or chronic. Although it is unlikely that double mutants arise simultaneously in clinical strains, the fact that they do happen at all suggests that having more than one resistanceassociated mutation confers a fitness advantage.…”
Section: Dna Sequence Variation Among Top 18 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance is a significant and mounting hurdle to the treatment and management of microbial disease (Wong and Kassen, 2011). The subsequent increase in quinolone resistance is currently undermining the clinical utility for various infections (Kim and Hooper, 2014).In particular, resistant P. aeruginosa infections are associated with adverse outcomes such as high mortality, morbidity, and expanded costs (Nathwaniet al, 2014).…”
Section: Introductionmentioning
confidence: 99%